The Anti-language in the English as a Foreign Language Curriculum - Neshkovska, Silvana (Respectus Philologicus, 2020)
The aim of this paper is to raise awareness of the significance of slang in educating well-rounded EFL learners. The study, first, uncovers the most salient features of slang, distinguishing it from jargon, argot, cant, etc. It also discusses the reasons why slang springs to life; the users of slang and functions it performs, as well as the word-formation processes employed in its creation.The paper further investigates the familiarity of Macedonian undergraduate students of English with currently relevant English and American slang, the main hypothesis being that they lack knowledge of slang due to insufficient exposure and instruction. The instruments used are a questionnaire and a quiz comprising 60 slang terms, intended to inspect informants’ knowledge of slang.The results obtained from this research confirm that slang is disregarded in EFL acquisition, and that no steady progress is made in the students’ knowledge of slang in the course of their university studies.